Chemical analysis of snus products from the United States and northern Europe. - Tameka S Lawler; Stephen B Stanfill; Hang T Tran; Grace E Lee; Patrick X Chen; J Brett Kimbrell; Joseph G Lisko; Carolina Fernandez; Samuel P Caudill; B Rey deCastro; Clifford H Watson (PLoS ONE)
Introduction Snus is an oral tobacco product that originated in Sweden. Snus products are available as fine-cut loose tobacco or in pre-portioned porous "pouches." Some snus products undergo tobacco pasteurization during manufacturing, a process that removes or reduces nitrite-forming microbes, resulting in less tobacco-specific nitrosamine content in the product. Some tobacco companies and researchers have suggested that snus is potentially less harmful than traditional tobacco and thus a potential smoking cessation aid or an alternative to continued cigarette consumption. Although snus is available in various countries, limited information exists on snus variants from different manufacturers. Methods Moisture, pH, nicotine, and tobacco-specific N'-nitrosamines (TSNAs) were quantified in 64 snus products made by 10 manufacturers in the United States and Northern Europe (NE). Reported means, standard errors, and differences are least-square (LS) estimates from bootstrapped mixed effects models, which accounted for correlation among repeated measurements. Minor alkaloids and select flavors were also measured. Results Among all product types, moisture (27.4%-59.5%), pH (pH 5.87-9.10), total nicotine (6.81-20.6 mg/g, wet), unprotonated nicotine (0.083-15.7 mg/g), and total TSNAs (390-4,910 ng/g) varied widely. The LS-mean unprotonated nicotine concentration of NE portion (7.72 mg/g, SE = 0.963) and NE loose (5.06 mg/g, SE = 1.26) snus were each significantly higher than US portion snus (1.00 mg/g, SE = 1.56). Concentrations of minor alkaloids varied most among products with the highest total nicotine levels. The LS-mean NNN+NNK were higher in snus sold in the US (1360 ng/g, SE = 207) than in NE (836 ng/g, SE = 132) countries. The most abundant flavor compounds detected were pulegone, eucalyptol, and menthol. Conclusion Physical and chemical characteristics of US and NE products labeled as snus can vary considerably and should not be considered "equivalent". Our findings could inform public health and policy decisions pertaining to snus exposure and potential adverse health effects associated with snus.